2018
DOI: 10.2298/abs171028003m
|View full text |Cite
|
Sign up to set email alerts
|

Combined mild hypoxia and bone marrow mesenchymal stem cells improve expansion and HOXB4 gene expression of human cord blood CD34+ stem cells

Abstract: How to cite this article: Mohammadali F, Abroun S, Atashi A. Combined mild hypoxia and bone marrow mesenchymal stem cells improve expansion and HOXB4 gene expression of human cord blood CD34+ stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Mesenchymal stromal cells (MSC) play an important role in the regulation of most cells of the BM microenvironment . From a therapeutic perspective, the administration of MSC has been shown to increase the engraftment ability and the hematopoietic function in preclinical models of xenotransplantation . In addition, it has been shown that the administration of MSC from third‐party donors can also potentially increase the engraftment and improve post‐transplant cytopenias .…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSC) play an important role in the regulation of most cells of the BM microenvironment . From a therapeutic perspective, the administration of MSC has been shown to increase the engraftment ability and the hematopoietic function in preclinical models of xenotransplantation . In addition, it has been shown that the administration of MSC from third‐party donors can also potentially increase the engraftment and improve post‐transplant cytopenias .…”
Section: Introductionmentioning
confidence: 99%
“…Since HSCs are deemed to grow in hypoxic environment (Takubo et al, 2010), low oxygen also plays an important role in the in vitro expansion of HSC. Under the condition of hypoxia, the expression of CXCR4 statistically increased, which means the ability of homing increased (Mohammadali et al, 2018). The use of p38-MAPK inhibitor (Bari et al, 2018) or antioxidants can maintain low ROS levels, protect HSCs from oxidative stress, and inhibit cell aging and differentiation (Ludin et al, 2014;Cao et al, 2016;Testa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They have strong proliferation and differentiation ability and can be multi-directionally differentiated into osteoblasts, chondrocytes, hematopoietic cells, muscle cells and other types of cells. They can be used to repair tissue and organ damage (Saito et al, 2018;Mohammadali, Abroun & Atashi, 2018). They have a hematopoietic support function, since they not only provide mechanical support for hematopoietic stem cells in the bone marrow but also secrete a variety of growth factors, such as interleukin (IL)-6, IL-11, leukemia inhibitory factor (LIF), macrophage colony-stimulating factor (M-CSF) and human stem cell growth factor (SCF), to support hematopoiesis (Amini et al, 2018;Mohammadali, Abroun & Atashi, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They can be used to repair tissue and organ damage (Saito et al, 2018;Mohammadali, Abroun & Atashi, 2018). They have a hematopoietic support function, since they not only provide mechanical support for hematopoietic stem cells in the bone marrow but also secrete a variety of growth factors, such as interleukin (IL)-6, IL-11, leukemia inhibitory factor (LIF), macrophage colony-stimulating factor (M-CSF) and human stem cell growth factor (SCF), to support hematopoiesis (Amini et al, 2018;Mohammadali, Abroun & Atashi, 2018). HBMSCs also regulate immune function and do not show immunological characteristics consistent with rejection (Liu et al, 2018;Gabr et al, 2017;Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%